Effect of Incorporating Hydroxyapatite and Zinc Oxide Nanoparticles on the Compressive Strength of White Mineral Trioxide Aggregate - Mahsa Eskandarinezhad; Mostafa Ghodrati; Fateme Pournaghi Azar; Farnaz Jafari; Parvin Samadi Pakchin; Amir Ardalan Abdollahi; AmirHouman Sadrhaghighi; Forouzan Rezvan (Shiraz University of Medical Sciences, 2021)
Statement of the Problem: Many efforts have been made to improve the properties of mineral trioxide aggregate (MTA), including the incorporation of nanoparticles. Purpose: The aim of this study was to investigate the incorporation of zinc oxide and hydroxyapatite nanoparticles on the compressive strength of white MTA (WMTA). Materials and Method: In this in vitro study, the following materials were evaluated: MTA, MTA+5% zinc oxide (ZnO) nanoparticles, MTA+10% zinc oxide nanoparticles, MTA+5% hydroxyapatite (HA) nanoparticles, MTA+10% zinc oxide nanoparticles. The compressive strength of the groups under investigation was measured on days 4 and 21 after mixing the MTA using a universal testing machine. Two-way ANOVA test was used to compare the groups and determine the significance of the effect of time and material on the compressive strength (p<0.05). Results: The highest and lowest compressive strength values were respectively measured for the second group, MTA/21 days, and the fourth group, MTA+Nano ZnO/4 days. Two-way ANOVA indicated that incorporation of zinc oxide and hydroxyapatite nanoparticles into MTA did not have a significant effect on compressive strength (p= 0.05). Compressive strength in all the groups increased over time from day 4 to day 21. However, this increase was not statistically significant (p= 0.06) except for the MTA group, which exhibited significant increase in compressive strength over time from day 4 to day 21 (p=0.007). Conclusion: Incorporation of HA and ZnO nanoparticles into MTA had no detrimental effects on its strength and these nanoparticles can be used to improve the other properties of MTA.